Silent Witnesses and Intercessors: Monastic Contribution in the Poetry of a Carthusian Monk - Hujanen, Riitta ca. 20./21. Jahrhundert (Irish theological quarterly, 2025)
The Carthusian monastic tradition, characterised by solitude and silence, has endured for more than nine centuries, largely unchanged, in the changing world. This article explores the theme of enclosed contemplative monastic contribution to the world based on textual analysis of an anonymous Carthusian monk’s poetry (written in the period 1964–2024) as well as other contemporary and early monastic literature. The study identifies two themes regarding monastic contribution: (1) the silent witness of eternity and of the Divine to the secular world; and (2) prayers of intercession. In addition, the monastic enclosed contemplative traditions appear to challenge modern society through some of their countercultural elements. Paradoxically, seen from the ancient monastic perspective, patience and hiddenness may prove more influential than short-term attention-seeking, and silence may contribute more to the world than the noise of social and other media.